14 - HIV/Aids at the Workplace: A Study of Corporate Responses to the HIV/Aids Pandemic in Zimbabwe - France Maphosa (CODESRIA Bulletin, 2003)
Zimbabwe has one of the highest HIV infection rates in the world, and they continue to increase. About one million people (10 percent of the population) had been infected with the HIV virus by December 1995 (SAFAids 1997: 1). By 2005 1.2 million people will have died of Aids, and cases of Aids will probably only begin to decline after 2010, about eight years after HIV prevalence rates begin to decline (IDS 1999: 34). The HIV/Aids epidemic has, perhaps inevitably, been perceived primarily as a health problem. However, as the magnitude of the problem becomes clearer, so does the recognition of how far-reaching and comprehensive the impact of HIV/Aids will be at the workplace and in the wider community. This is largely because infection is highest among the economically most productive groups. Chitiyo (1990 quoted by Jackson 1992) states that 90 percent of people infected with HIV are employed. As the Aids threat conti-nues to affect the workplace, employers will increasingly require policies and mechanisms for dealing with personnel issues such as absenteeism, sick leave, ill health and early retirement.